2012
DOI: 10.2147/nbhiv.s36549
|View full text |Cite
|
Sign up to set email alerts
|

Baseline medication adherence and response to an electronically delivered health literacy intervention targeting adherence

Abstract: Medication adherence in persons treated for human immunodeficiency virus (HIV) continues to be an important focus for intervention. While high levels of adherence are required for good clinical outcomes, research shows many patients do not achieve these levels. Despite multiple interventions to improve adherence, most require multiple sessions delivered by trained clinicians. Cost and lack of trained personnel limit the availability of these interventions. Alternatives to clinician-delivered interventions are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
78
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(78 citation statements)
references
References 30 publications
0
78
0
Order By: Relevance
“…Indeed, several scholars claimed that specific interventions tailored to the individual levels of health literacy should be devised to improve medication adherence of people with limited health literacy skills. 46 On the contrary, Colbert and colleagues 47 suggested that perceived self-efficacy deeply affects medication adherence, while functional health literacy is not related to either medication adherence or self-efficacy beliefs. Moreover, a recent study about adolescents living with HIV infection showed that health literacy affected neither medication adherence nor self-efficacy perception, even after controlling for age and education levels.…”
Section: Simondsmentioning
confidence: 99%
“…Indeed, several scholars claimed that specific interventions tailored to the individual levels of health literacy should be devised to improve medication adherence of people with limited health literacy skills. 46 On the contrary, Colbert and colleagues 47 suggested that perceived self-efficacy deeply affects medication adherence, while functional health literacy is not related to either medication adherence or self-efficacy beliefs. Moreover, a recent study about adolescents living with HIV infection showed that health literacy affected neither medication adherence nor self-efficacy perception, even after controlling for age and education levels.…”
Section: Simondsmentioning
confidence: 99%
“…Although one RCT scored 8 of 13 [23] and one of three quasi-experimental studies scored 6 of 9, [24] they had strengthened validity of causal inferences by comparing control and intervention groups. In addition, two quasi-experimental studies scored 6 of 9 [25,26] and lacked a comparison group to determine pre-post intervention effects.…”
Section: Characterizing the Evidence Basementioning
confidence: 99%
“…Four studies were conducted in the U.S., [24][25][26][27] two in Uganda, [23,28] and one in Peru. [29] Various study designs were used: cross-sectional, [27][28][29] quasi-experimental, [24][25][26] and a RCT. [23] Two studies identified a theoretical or conceptual framework used in their research.…”
Section: Overview Of Studies Included In the Reviewmentioning
confidence: 99%
See 2 more Smart Citations